Abnormal embryos of sharpnose sharks, Rhizoprionodon porosus and Rhizoprionodon lalandii (Elasmobranchii: Carcharhinidae), from Brazilian coast, western South Atlantic - Dos Santos, Camila Mayumi Hirata [UNESP]; Gadig, Otto Bismarck Fazzano [UNESP] (Cambridge University Press (CUP), 2014)
This study presents the second worldwide report on abnormal embryos of the sharpnose sharks, Rhizoprionodon, based on the two species (Rhizoprionodon porosus and Rhizoprionodon lalandii) occurring on the Brazilian coast. For R. porosus two conjoined twin embryos showing complete duplication of the vertebral column, viscera and several external structures (head, first and second dorsal fins, pectoral fins), and scoliosis in both axis at the pelvic fin level are reported. The three embryos of R. lalandii exhibited numerous lordosis and kyphosis along the entire vertebral column. The possible relationship between anomalies and the human major threats to sharks is discussed based on previous reproductive, genetic and ecotoxicological studies on R. lalandii for southern Brazil.
Keywords: anatomy; anomaly; conservation; elasmobranch; morphology